O curso de enfermagem da UFS e a trajetória histórica das práticas do cuidado : da criação do Departamento de Saúde Pública a consolidação do campo em Sergipe (1931-1979) - Silva, Elizabete Farias Lima (2022)
The present study presents as an object the historical trajectory between nursing care practices and the creation of the Undergraduate Nursing Course, a cut out between 1931 and 1979. Periods between the creation of the Department of Public Health of Sergipe and the higher education of the first class of the Undergraduate Nursing Course of UFS, respectively. The aim of this study is to analyze the historical trajectory between nursing care practices and the creation of the Undergraduate Nursing course at the Federal University of Sergipe, from 1931 to 1979, follow as specific objectives: to identify the phenomena in the health field, which proposed a reflection on nursing care practices, in Sergipe society, from the point of view of the History of Education; describe the reasons and motivations that determine these practices, which contributed to the creation of the nursing course at UFS; present in the curricular matrix of the nursing course of UFS, the scientific technical proposal and the profile of the graduate inserted in this society; to reflect on the improvement of nursing care practices in Sergipe society, in the light of Pierre Bourdieu's theory of social structures. It is a study of historicalsocial nature, with a qualitative approach, based on cultural history, whose sources were documents, minutes, iconography and other physical and electronic writings responsible for the composition and preservation of the history of care practices and the creation of the undergraduate nursing course at the Federal University of Sergipe, looking at the constant dialogue between the author and other details, to be: absence of documents, social, economic and political context local and national. The possible voids and gaps emerged in the temporal space were met through the oral history of the social characters who contributed and/or witnessed the social phenomena that occurred in the historical trajectory proposed in this study. The process of analysis of the collected data was supported from the concepts signed by the French sociologist, Pierre Bourdieu, based on the theory of social structures, based on key concepts, namely: habitus, field, symbolic or cultural systems. According to the above, in the discussion about nursing care practices, the screen study revealed that care and practices were improved under the influence of aspects of knowledge, where scientificism stood out in a hegemonic way, with the creation of the Undergraduate Nursing Course of the Federal University of Sergipe, a theme where an inexhaustible agenda to research is raised, justified by publications, still timid, concerning the understanding and understanding of events, sociopolitical contextualization and confrontations fought by characters committed to promoting modern nursing throughout the Sergipe territory. And under this lens, the present study rests.